Analisis dan Pemetaan Limpasan Permukaan di DAS Citanduy Hulu dengan Metode SCSN - Asep Kurnia Hidayat; Pengki Irawan; Jaza'ul Ikhsan; Sri Atmadja; Novia Komala Sari (Rona Teknik Pertanian, 2021)
Abstrak. DAS Citanduy merupakan salah DAS yang terbesar di pulau Jawa dengan sungai utama adalah Cintanduy. DAS Citanduy terdiri dari beberapa sub DAS, salah satunya adalah sub DAS Citanduy Hulu. Perubahan tata guna lahan di DAS Citanduy Hulu terus terjadi, kondisi tsb telah mengakibatkan peningkatan debit banjir di sungai. Peningkatan debit di sungai diakibatkan adanya limpasan permukaan akibat hujan. limpasan permukaan dapat dianalisis menggunakan metode SCS (Soil Conservation Service). Metode SCS juga dianalisis berdasarkan kondisi tanah, sehingga dapat menentukan nilai Curve Number (CN) dari lahan. Hasil analisis tahun 2018, menunjukkan bahwa tutupan lahan 18,99% atau 13.735,97 ha berupa hutan (hutan primer, sekunder dan hutan tanaman). Sebaran jenis tanah di umumnya adalah Typic Dystrudepts (36,57%) dan Typic Hapludands (37,93%). Hydrological Soil Group (HSG) di DAS Citanduy Hulu didominasi oleh klas B sebesar 76, 92 %. Hasil analisis didapatkan bahwa DAS Citanduy Hulu tebal runoff maksimum pada PUH 2, 5, 10, 25, dan 50 tahun secara berurutan adalah 104 mm, 133 mm, 147 mm, 171 mm dan 187 mm. Tebal limpasan permukaan minimum dengan PUH 2, 5, 10, 25 dan 50 tahun secara berurutan adalah 17 mm, 31 mm, 39 mm, 53 mm dan 64 mm. Tebal limpasan permukaan menunjukkan potensi peningkatan debit banjir.Analysis And Mapping Runoff In Watershed Upper Citanduy With SCSN MethodAbstract. Citanduy watershed is one of the largest watersheds on the island of Java with the main river being Cintanduy. The Citanduy watershed consists of several sub-watersheds, one of which is the Upper Citanduy sub-watershed. Changes in land use in the Upper Citanduy watershed continue to occur, this condition has resulted in an increase in flood discharge in the river. The increase in discharge in the river is caused by surface runoff due to rain. Surface runoff can be analyzed using the SCS (Soil Conservation Service) method. The SCS method is also analyzed based on soil conditions so that it can determine the Curve Number (CN) value of the land. The results of the 2018 analysis show that 18.99% or 13,735.97 ha of land cover is forest (primary, secondary and plantation forests). The distribution of soil types, in general, is Typic Dystrudepts (36.57%) and Typic Hapludands (37.93%). Hydrological Soil Group (HSG) in the Upper Citanduy watershed is dominated by class B by 76.92%. The results of the analysis showed that the maximum runoff thickness of the Upper Citanduy Watershed at PUH 2, 5, 10, 25, and 50 years respectively was 104 mm, 133 mm, 147 mm, 171 mm, and 187 mm. The minimum surface runoff thickness with PUH 2, 5, 10, 25, and 50 years respectively is 17 mm, 31 mm, 39 mm, 53 mm, and 64 mm. The thickness of the surface runoff indicates the potential for increased flood discharge.